DEVELOPMENT OF HIGHER ORDER THINKING SKILLS (HOTS) QUESTIONS ON METABOLISM MATERIAL TO EMPOWER CRITICAL THINKING OF GRADE XII SENIOR HIGH SCHOOL STUDENTS - Vioni Jilia Eka Putri; Evi Suryawati; Fitra Suzanti (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This study aims to produce a feasible Higher Order Thinking Skills (HOTS) test instrument to measure the critical thinking abilities of Grade XII senior high school students on metabolism material. The type of research used in this study is Research and Development (R&D) with qualitative and quantitative approaches. The R&D research method is used to develop Higher Order Thinking Skills (HOTS) test items on metabolism material to empower the critical thinking of Grade XII senior high school students. The development model used in this study is the Borg & Gall (1983) model. According to Borg & Gall, development research is oriented toward developing and validating products used in education. The product to be developed in this study consists of Higher Order Thinking Skills (HOTS) questions on Biology material for the odd semester. The sequence of development research stages proposed by Borg & Gall consists of seven stages, namely: 1) research and information collecting, 2) planning, 3) developing a preliminary form of the product, 4) preliminary field testing, 5) main product revision, 6) main field testing, and 7) final product revision. The results of the study indicate that the developed Higher Order Thinking Skills (HOTS) test instrument on metabolism material has met the feasibility criteria as a tool for measuring the critical thinking abilities of Grade XII students. This confirms that the instrument is capable of proportionally measuring students’ critical thinking skills and can be used as an evaluation tool for biology learning based on Higher Order Thinking Skills (HOTS).